The perfect Torah - Neusner, Jacob, 1932-2016 (Brill reference library of Judaism, 2003)
Jacob Neusner demonstrates in this analysis that the perfect Torah is the medium through which the one, unique God makes himself known. The Judaic statement of monotheism comes to expression in scripture as perfected by the Oral Torah in its native category-formations, Halakhah and Aggadah.